The HOMO-LUMO Gap as Discriminator of Biotic from Abiotic Chemistries - Roman Abrosimov; Bernd Moosmann (Life, 2024)
Low-molecular-mass organic chemicals are widely discussed as potential indicators of life in extraterrestrial habitats. However, demarcation lines between biotic chemicals and abiotic chemicals have been difficult to define. Here, we have analyzed the potential utility of the quantum chemical property, HOMO-LUMO gap (HLG), as a novel proxy variable of life, since a significant trend towards incrementally smaller HLGs has been described in the genetically encoded amino acids. The HLG is a zeroth-order predictor of chemical reactivity. Comparing a set of 134 abiotic organic molecules recovered from meteorites, with 570 microbial and plant secondary metabolites thought to be exclusively biotic, we found that the average HLG of biotic molecules was significantly narrower (−10.4 ± 0.9 eV versus −12.4 ± 1.6 eV), with an effect size of g = 1.87. Limitation to hydrophilic molecules (XlogP < 2) improved the separation of biotic from abiotic compounds (g = 2.52). The “hydrophilic reactivity” quadrant defined by |HLG| < 11.25 eV and XlogP < 2 was populated exclusively by 183 biotic compounds and 6 abiotic compounds, 5 of which were nucleobases. We conclude that hydrophilic molecules with small HLGs represent valuable indicators of biotic activity, and we discuss the evolutionary plausibility of this inference.